Optimising Flood Risk Reduction in Bali's Provincial Government Center through Cultural Philosophy Approach and GIS-based Conservation of Infiltration Wells - Tri Hayatining Pamungkas; Mawiti Infantri Yekti; Kadek Budhi Warsana (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Bali's administrative center, Renon Village, faces an increased risk of flooding due to land cover change. Conservation is needed to reduce this risk by improving water infiltration capacity. Infiltration wells are a solution to increase infiltration capacity. The Tri Hita Karana concept approach, especially Palemahan, in Balinese culture is adopted to implement infiltration well conservation with the support of GIS technology and by flood regulations and infiltration wells. The analysis showed that with a land area of 100 m2, the dimensions of the infiltration well were obtained in diameter of 1 m, and a depth of 2 m with a total of 2 pieces could absorb 2.46 m3 of rainwater. The application of infiltration wells in the study area can reduce the discharge and volume of flood peaks of 2 years, 5 years, 10 years, 25 years, 50 years, 100 years, and 200-year flood peaks, effectively reducing from 8.61% to 31.24%. This research supports the planning of sustainable drainage with a Low Impact Development approach. In addition, the construction of infiltration wells also contributes to preserving water conservation and applying green buildings that are environmentally friendly and energy efficient.